Single-nucleus transcriptomes reveal the underlying mechanisms of dynamic whitening in thermogenic adipose tissue in goats - Manman Li; Nange Ma; Shujie Luo; Yuyi Lu; Xixi Yan; Yang Li; Xinmei Li; Zhuohui Li; Zhipei Wu; Zhenyu Wei; Wei Wang; Huimei Fan; et al. (Journal of Animal Science and Biotechnology)
Abstract Background Thermogenic adipose tissue, both beige and brown, experiences whitening as animals are exposed to warmth and age, but the potential mechanisms are not fully understood. In this study, we employed single-nucleus RNA-seq to construct a cell atlas during whitening progression and identified the characteristics of thermogenic adipocytes. Results Our histological studies and bulk transcriptome gene expression analysis confirmed that both perirenal and omental adipose tissues (pAT and oAT) exhibited progressive whitening in goats. Compared to the classic brown adipocytes in mice, goat thermogenic adipocytes were more closely related in gene expression patterns to human beige adipocytes, which was also confirmed by adipocyte type- and lineage-specific marker expression analysis. Furthermore, trajectory analysis revealed beige- and white-like adipocytes deriving from a common origin, coexisting and undergoing the transdifferentiation. In addition, differences in gene expression profiles and cell communication patterns (e.g., FGF and CALCR signaling) between oAT and pAT suggested a lower thermogenic capacity of oAT than that of pAT. Conclusions We constructed a cell atlas of goat pAT and oAT and descripted the characteristics of thermogenic adipocytes during whitening progression. Altogether, our results make a significant contribution to the molecular and cellular mechanisms behind the whitening of thermogenic adipocytes, and providing new insights into obesity prevention in humans and cold adaptation in animals.